Ергономічні вимоги до формування візуальних комунікацій для маломобільних груп населення - Линник, Ірина Едуардівна; Шкляр, Світлана Петрівна (НТУ "ХПІ", 2017)
Проаналізовано інформативність, як одну з основних ергономічних вимог до якості середовища життєдіяльності маломобільних груп населення. Зазначено головні функції засобів візуальної інформації. Сформульовано принципи організації системи візуальних комунікацій для маломобільних груп населення: комплексності, цільової спрямованості, легкості сприйняття, безпечності, надійності, економічності, естетичності. Визначено вимоги до засобів візуальної інформації. Наведено деякі вимоги до вивісок (їхній формі, кольору, шрифту, освітленню), динамічних інформаційних знаків, додаткових орієнтирів на вулицях, візуальної різноманітності зони відпочинку.

Informativeness was analyzed as one of the main ergonomic requirements to the quality of life of low mobility groups. The main functions of the visual information tools are indicated. The principles of the organization of the system for visual communications for low-mobility groups of the population are formulated: complexity, purpose orientation, ease of perception, safety, reliability, economy, and aesthetics. Determined the requirements for visual information that allows people to easily navigate in space ; Be coherent, simple in configuration, well illuminated in the evening and easy to perceive; for visually impaired persons, it is possible to use signs with big letters and place them at a height of 1,5 m above ground level so that they can be felt by hand; determine the location of service establishments; mark entrances to the building and their functional purpose; inform about services and help to choose the shortest ways to move around. Requirements for signboards (their form, color, font, and illumination), dynamic information signs, additional directions on the streets, visual diversity of the recreation zone are given.
Ergonomic Requirements for the Formation of Visual Communications for Low-Mobile Population Groups
Keywords: інформативність; середовище; люди з обмеженими можливостями; informativeness; visual communication